Biomass-Based Antifouling Coatings: Mechanisms, Materials, Applications, and Emerging Sustainable Strategies - Wei, Yudi; Maršík, Dominik; Thoresen, Petter Paulsen; Matsakas, Leonidas; Shi, Yijun (Nano-Micro Letters, 2026)
Biofouling remains a critical challenge across marine, medical, and industrial sectors, driving the need for sustainable and eco-friendly antifouling coatings. Biomass-based materials, including lignin, tannins, betaines, polysaccharides, and proteins, have emerged as promising candidates due to their biocompatibility, biodegradability, and diverse antifouling mechanisms. These materials inhibit biofouling through mechanisms such as hydration layer formation, surface charge repulsion, hydrophobic foul-release, and biocidal effects, offering effective resistance to protein adsorption, bacterial attachment, and biofilm formation. This review provides a comprehensive overview of recent advancements in biomass-based antifouling coatings, focusing on their antifouling mechanisms, synthesis methods, and applications. Key challenges concerning mechanical durability and scalability are explored, along with potential approaches to enhance the development of sustainable antifouling technologies. Highlights: 1 This review systematically categorizes biomass-based antifouling coatings based on lignin, tannins, betaines, polysaccharides and proteins, highlighting how their intrinsic chemistries contribute to antifouling interfaces. 2 The review clarifies how hydration layers, foul-release interfaces, surface charge regulation and biocidal actions collectively contribute to antifouling performance. 3 Key chemical and physical crosslinking strategies are compared to highlight their roles in enhancing mechanical integrity and long-term stability. 4 Critical bottlenecks in durability, adhesion, validation and scalability are identified, and potential routes for future technological development are outlined.